Perovskite superstructures and heterostructures for enhanced optical performance - Chan, Wen Kiat (Nanyang Technological University, 2023)
Perovskites as a material class have attracted immense research attention due to its highly tunable emissions, narrow full width at half maximum, high photoluminescence quantum yields, broad absorption spectra, defect tolerance, and large carrier diffusion length. While much progress has been accomplished in perovskite research, two areas are relatively unexplored and will be the focus of this thesis. The first is perovskite superstructures (SSs), which have only been reported as recently as 2018. Studies on perovskite SSs are gradually garnering attention as perovskite SSs allow for the electronic coupling of their constituent nanocrystals (NCs), allowing for the interdot effect and superradiant burst emissions. The second area is the formation of heterostructures, which allow for the combination of two different materials with complementary optical properties. For instance, combining lanthanide nanoparticles (LnNPs) with perovskites allows for enhanced absorption and two-way energy transfer. The first project in this thesis addresses the mechanism of perovskite SS formation which has thus far have not been studied in detail. In this work, CsPbBr3 perovskites were synthesized using different experiment conditions and quantities of PbBr2 precursor, and the total red-shift of the resulting samples were analysed to quantify the formation of perovskite SSs. From this study, we found that PbBr2 plays a critical role in CsPbBr3 SS formation. Since PbBr2 occupies Br vacancies naturally occurring on CsPbBr3 NCs, we proposed a possible SS formation mechanism where PbBr2 serves as a ‘glue’ linking together individual NCs to form SSs at higher PbBr2 concentrations. At lower PbBr2 concentrations the CsPbBr3 SSs demerge into individual CsPbBr3 NCs. The second project for this thesis addresses the formation of hybrid organic-inorganic perovskite SSs. Studies involving perovskite SSs mainly focus on all-inorganic CsPbBr3 synthesized using either the hot injection or ultrasonication methods. Hybrid perovskites involving cations such as MA and FA are valuable for their ultrapure green emissions and have been used for the highest performance perovskite solar cells. In this work, MA/FA/CsPbBr3 perovskite SSs were synthesized using the more scalable and facile ligand-assisted reprecipitation (LARP) method, demonstrating both the existence of hybrid perovskite SSs and the potential of the LARP method in obtaining perovskite SSs. The SSs drop-casted onto thin films produce ultrapure green emissions, demonstrating the potential for device fabrication in display applications. The last work of thesis focuses on the formation of LnNP@perovskite core-shell heterostructures. Lead halide perovskites and lanthanide ions have complementary absorption spectra and combining them allows for multiple energy transfer pathways depending on the permutation used. The formation of LnNP@perovskite heterostructures is rarely reported due to the challenges in overcoming the lattice mismatch between LnNPs and perovskites. In this thesis, we present a strategy to overcome the lattice mismatch by using ultrasmall LnNPs to seed the growth of perovskites, resulting in LnNP@perovskite heterostructures. The heterostructures demonstrated two-way energy transfer and could be activated with ultraviolet or near-infrared light. In conclusion, this thesis provided insights into perovskite SS formation, developed hybrid SS perovskites with ultrapure green emissions, and highlighted a strategy to overcome the lattice mismatch to form LnNP@perovskite heterostructures. While there is a lot more to be explored and learned, we hope that this work will contribute to the further development of perovskite devices with enhanced optical performance.